The Role of Organizational Commitment in Mediating the Influence of Leadership and Integrity on the Performance of Employees at the Maluku High Prosecutor's Office: Peran Komitmen Organisasi dalam Memediasi Pengaruh Kepemimpinan dan Integritas terhadap Kinerja Pegawai di Kejaksaan Tinggi Maluku - Ulfa Sakinah Lating; Nanik Kustiningsih; Sri Rahayu (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study investigates how integrity and leadership influence organizational performance, with organizational commitment as a mediating factor, focusing on 140 permanent employees at the Maluku High Prosecutor’s Office in Indonesia. A quantitative approach was employed using questionnaires, and data were analyzed using SPSS through descriptive and inferential statistical techniques. Results show that both leadership and integrity have a positive and significant impact on organizational performance. Leadership also strengthens organizational commitment, which in turn enhances performance. Notably, organizational commitment fully mediates the relationship between integrity and performance, indicating its critical role in translating ethical behavior into effective outcomes. These findings imply that public institutions should prioritize ethical leadership development and foster a culture of integrity and commitment to improve overall performance. Strengthening these internal values can lead to more accountable, efficient, and effective public service delivery.